Isolation and characterisation of CPRGA3 in papaya induced by Erwinia mallotivora - Mohamed Abu Bakar, Nur Syazana (2019)
Papaya dieback disease is rapidly progressing and has been negatively affecting Malaysian papaya export industry. Due to the complex nature of plant disease resistance mechanisms, development of papaya variety that is resistant to dieback disease has remained a great challenge. Thus, characterisation of resistance gene analogs (RGAs) in papaya could be an alternative to understand disease resistance in papaya. RGAs are potential plant resistance (R) genes that mainly encode for nucleotide binding site (NBS) and leucine rich repeat (LRR) domains. Although NBS-LRR gene is essential in pathogen recognition and defense signaling, NBS-LRR gene can be also be found mediating plant disease susceptibility. In this study, CpRGA3 sequences of dieback tolerant papaya, Viorica and dieback susceptible papaya, Eksotika was isolated and analyzed following infection by Erwinia mallotivora. Sequencing results revealed a single nucleotide polymorphism (SNP) at three positions in CpRGA3 of Viorica papaya resulting in amino acid changes. Interestingly, a change from lysine to arginine at the first position lies in the conserved LRR domain. On the other hand, phylogenetic analysis showed CpRGA3 was closely related with RGA2 and RGA3 from other plant species. Structural analysis showed that there were differences in the secondary structure where CpRGA3-Viorica have 15 α-helix while CpRGA3-Eksotika have 13 α-helix and amino acid residues involved at the ligand binding surface of CpRGA3 from Viorica and Eksotika varies. The SNP at LRR domain might contribute to the structural differences of CpRGA3 protein observed in Viorica and Eksotika, which then resulting in the tolerant and susceptible phenotype respectively. However, when superimposed, the two proteins did not have any structural differences. Next, the gene expression pattern of CpRGA3 in response to E. mallotivora was determined through RT-PCR analysis. Despite having the characteristic features of an RGA, the result showed that CpRGA3 was up-regulated at 48 hpi with relative band intensity at 8.7 in Eksotika papaya but with low expression (less than 0.5) in Viorica papaya. Furthermore, disease symptoms development was observed in transgenic papaya over-expressing CpRGA3. Transient overexpression of CpRGA3 in Eksotika papaya expedited the onset of dieback disease symptoms following inoculation with E. mallotivora by three days. Overall, this study suggests that CpRGA3 encoding NBS-LRR mediates disease susceptibility to E. mallotivora in papaya. This study provides new insight into the role of NBS-LRR genes in disease susceptibility that could implicates the enhancement of plant disease resistance and the overall strategy for plant disease management in the future.